Containment of COVID-19 cases among healthcare workers: The role of surveillance, early detection, and outbreak management. (11th July 2020) - Wee, Liang En; Sim, Xiang Ying Jean; Conceicao, Edwin Philip; Aung, May Kyawt; Goh, Jia Qing; Yeo, Dennis Wu Ting; Gan, Wee Hoe; Chua, Ying Ying; Wijaya, Limin; Tan, Thuan Tong; Tan, Ban Hock; Ling, Moi Lin; et al.
Abstract: Objective: Staff surveillance is crucial during the containment phase of a pandemic to help reduce potential healthcare-associated transmission and sustain good staff morale. During an outbreak of SARS-COV-2 with community transmission, our institution used an integrated strategy for early detection and containment of COVID-19 cases among healthcare workers (HCWs). Methods: Our strategy comprised 3 key components: (1) enforcing reporting of HCWs with acute respiratory illness (ARI) to our institution's staff clinic for monitoring; (2) conducting ongoing syndromic surveillance to obtain early warning of potential clusters of COVID-19; and (3) outbreak investigation and management. Results: Over a 16-week surveillance period, we detected 14 cases of COVID-19 among HCWs with ARI symptoms. Two of the cases were linked epidemiologically and thus constituted a COVID-19 cluster with intrahospital HCW–HCW transmission; we also detected 1 family cluster and 2 clusters among HCWs who shared accommodation. No transmission to HCWs or patients was detected after containment measures were instituted. Early detection minimized the number of HCWs requiring quarantine, hence preserving continuity of service during an ongoing pandemic. Conclusions: An integrated surveillance strategy, outbreak management, and encouraging individual responsibility were successful in early detection of clusters of COVID-19 among HCWs. With ongoing local transmission, vigilance must be maintained for intrahospital spread in nonclinical areas where social mingling of HCWs occurs. Because most individuals with COVID-19 have mild symptoms, addressing presenteeism is crucial to minimize potential staff and patient exposure.